Effects of Self-Directed and Cooperative Learning Strategies on Junior Secondary School Students’ Learning Outcomes in Fine Arts in Ogun State, Nigeria (2014)
Fine Arts is one of the five themes broadly taught under Cultural and Creative Arts subjects at the junior secondary school level, which facilitate transfer of knowledge and have practical application in other subject areas. These qualities notwithstanding,many students are still deficient in the rudiments of fine arts (principles and elements of art/ application of colours), and this contribute to the persistent decline in students‟ learning outcomes. Despite the focus of previous researchers on different methods such as computer-assisted instruction and videotape as means of improving students‟ achievement in fine arts, their performance in the subject has not improved. Hence, this calls for the strategies that do not require highly technical facilities that will center on hand-on/mind-on activities such as Self-Directed Learning (SDL) and Cooperative Learning (CL). This study, therefore, examined the effects of SDL and CL Strategies on students‟ achievement in and attitude to fine arts. The moderating effect of creative ability and parental influence were also determined.The study adopted the pretest-posttest, control group, quasi-experimental design. Participants comprised six intact classes of JS2 made up of 180 students from six purposively selected secondary schools in Ogun East Senatorial district. The schools were randomly assigned to Self-Directed Learning, Cooperative Learning and Conventional Method (CON) groups. The treatment lasted six weeks. Four instruments were used: Fine Arts Achievement Test (r = 0.73); Students‟ attitude to Fine Arts Questionnaire (r = 0.72); Creative Ability Test (r = 0.730) and Parental Influence Scale (r = 0.83). Instructional guides for each of the experimental and control groups were employed. Seven null hypotheses were tested at 0.05 level of significance. Data were analysed using Analysis of Covariance and Scheffe‟s post hoc analysis.Treatment had significant main effects on students‟ achievement in Fine Arts (F(2, 165) = 3.67; η2 =.43). Those exposed to SDL had higher achievement mean score (x=21.91), followed by CL (x =20.57) and CON ( x =17.89) respectively. There was a significant main effect of treatment on students‟ attitude to Fine Arts (F(2, 165) = 7.202; η2 = .80). Participants in SDL had higher attitude mean score ( x =84.0) than the CL ( x =83.65) and CON ( x =72.11). There was no significant main effect of creative ability on students‟ achievement in and attitude to fine arts. There was also no significant main effect of parental influence on students‟ achievement in and attitude to Fine Arts. Furthermore, there was no significant interaction effect on parental influence and creative ability on students‟ achievement in and attitude to Fine Arts.Self-directed and Cooperative Learning Strategies enhanced students‟ achievement in and attitude to fine arts. Fine arts teachers in secondary schools should therefore adopt both strategies for improving learning outcomes. Also there is need to train Fine Arts teachers in the use of the strategies